2017
DOI: 10.3389/fimmu.2017.00793
|View full text |Cite
|
Sign up to set email alerts
|

The Affinity of Elongated Membrane-Tethered Ligands Determines Potency of T Cell Receptor Triggering

Abstract: T lymphocytes are important mediators of adoptive immunity but the mechanism of T cell receptor (TCR) triggering remains uncertain. The interspatial distance between engaged T cells and antigen-presenting cells (APCs) is believed to be important for topological rearrangement of membrane tyrosine phosphatases and initiation of TCR signaling. We investigated the relationship between ligand topology and affinity by generating a series of artificial APCs that express membrane-tethered anti-CD3 scFv with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 91 publications
7
48
0
Order By: Relevance
“…By contrast, recent reports have shown that mechanical forces specifically applied to TCRs can initiate signaling in T cells ( 18 20 ), which may not require CD45 segregation for T cell activation. In addition, we recently reported that a high-affinity membrane-tethered anti-CD3 antibody effectively triggered TCR signaling even when elongated with very long tethers ( 21 ), which is not expected to effectively cause CD45 to physically segregate from engaged TCR complexes. The role of CD45 in initiation of TCR signaling is, therefore, uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, recent reports have shown that mechanical forces specifically applied to TCRs can initiate signaling in T cells ( 18 20 ), which may not require CD45 segregation for T cell activation. In addition, we recently reported that a high-affinity membrane-tethered anti-CD3 antibody effectively triggered TCR signaling even when elongated with very long tethers ( 21 ), which is not expected to effectively cause CD45 to physically segregate from engaged TCR complexes. The role of CD45 in initiation of TCR signaling is, therefore, uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…We modulated the molecular topology of proteolipid surfaces by varying the lengths of the tethered anti-CD3 scFv. By addition of a short tether corresponding to one immunoglobulin (Ig)-like domain (~3.5 nm) ( 22 ) or a longer tether derived from the CD43 extracellular domain [19–45 nm depending on the measurement method ( 21 , 23 )], we could generate different dimensions of chimeric molecules. We examined a high-affinity anti-CD3 scFv (OKT3) that can activate T cells regardless of tether dimensions and a low-affinity anti-CD3 variant (OKT3 MA ) that can activate T cells when anchored to cells via a short but not long tether ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, all experiments testing axial positioning of TCR ligands have involved either the extension of TCR ligand height 12, 14 or the truncation of the CD45 extracellular domain 15, 16 . These flexible or “soft matter” approaches have non-linear effects on the inter-membrane spacing 12, 14, 17 and thus lateral spacing and affinity 18 . These caveats make it difficult to distinguish competing models 14, 15 .…”
mentioning
confidence: 99%
“…These flexible or “soft matter” approaches have non-linear effects on the inter-membrane spacing 12, 14, 17 and thus lateral spacing and affinity 18 . These caveats make it difficult to distinguish competing models 14, 15 . If extension could be accomplished with a rigid, non-tilting structure, this would enable a more precise test of the KS model and a better general understanding of TCR triggering.…”
mentioning
confidence: 99%